Tap setting transformer for loss minimization using genetic algorithm / Mazyudin Mokhtar - Mokhtar, Mazyudin (2007)
This paper presents an alternative approach to the use of load flow by incorporation Genetic Algorithm (GA) to search the optimal transformer tap setting in order to minimize losses. The choice of transformer tap setting can be determined whilst minimizing losses. The performance of this GA technique is to be tested using standard IEEE 6-bus and IEEE 30-bus system for its capability and feasibility. All simulations are done using Matlab program version 7.0